2009
DOI: 10.1037/a0016108
|View full text |Cite
|
Sign up to set email alerts
|

The communication of emotion via touch.

Abstract: The study of emotional communication has focused predominantly on the facial and vocal channels but has ignored the tactile channel. Participants in the current study were allowed to touch an unacquainted partner on the whole body to communicate distinct emotions. Of interest was how accurately the person being touched decoded the intended emotions without seeing the tactile stimulation. The data indicated that anger, fear, disgust, love, gratitude, and sympathy were decoded at greater than chance levels, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
380
7
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 433 publications
(434 citation statements)
references
References 30 publications
(45 reference statements)
19
380
7
8
Order By: Relevance
“…Hertenstein et al (2006) reported no influence of the gender of decoders and encoders on the success of emotional communication, a result confirmed in a more recent study with 124 dyads (Hertenstein et al 2009). In the light of their results, and given the constraints of the present study, gender was allowed to be confounded to some degree with the couple/stranger factor, in an unbalanced design in which most decoders received touch from opposite gender romantic partners, and same gender strangers.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…Hertenstein et al (2006) reported no influence of the gender of decoders and encoders on the success of emotional communication, a result confirmed in a more recent study with 124 dyads (Hertenstein et al 2009). In the light of their results, and given the constraints of the present study, gender was allowed to be confounded to some degree with the couple/stranger factor, in an unbalanced design in which most decoders received touch from opposite gender romantic partners, and same gender strangers.…”
Section: Resultssupporting
confidence: 69%
“…The interaction between Group and Relationship status was completely absent (F<1), with the same mean advantage in accuracy of 1.6 for partners over strangers in each Group. While acknowledging the low power of this analysis, taken together with the results reported by Hertenstein et al (2006Hertenstein et al ( , 2009 we were confident that our results were unlikely to reflect gender effects to any significant extent.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…(8) Due to different sensory stimuli in childhood, adolescence and the adult phase, the emotions between men and women are also distinct. (9) Differences are clear, as well as their effects and the singular gender description of who touches and is touched. (10) This study favored the discussion among the students about their behavior and that of the patients with mental disorders, (4) reducing obstacles in the form of perceiving it.…”
Section: Discussionmentioning
confidence: 99%
“…Still, interpersonal touch is still used in intimate relationships, as it is an important form of communication for conveying intimate emotions such as love and sympathy [3]. Indeed recent studies have shown that basic emotions, e.g., anger, fear, and happiness, can be communicated through touch only [4,5].…”
Section: Introductionmentioning
confidence: 99%